Noise exposure during orthopaedics surgery - Razali, Ailin; Herman, Hendy Putra; Zulkifly, Ahmad Hafiz (Zibeline International Publishing, 2017)
There is serious concern on noise hazard in operating theatre especially in the orthopaedics field that requires usage of many instruments. However, data on this noise exposure particularly in Malaysia is rather limited. This study was conducted as a pilot study to investigate the noise exposure in orthopaedics theatre in a hospital in Kuantan, Pahang in June 2011. Several different orthopaedics theatres involving procedures that use powered instruments were investigated. Time recorded noise exposures were taken using personal noise dosimeters throughout the surgeries worn by the surgeons. The peak noise level and the average noise exposure within 8 hours were determined, and compared with the available Factory and Machinery Act (Noise) standards. Six out of seven surgeries exceeded 140 dBA for peak sound levels. The average noise exposure within 8 hours was below 85 dBA in all cases. Although the average noise level did not surpass the stipulated guidelines, the peak level exceeding 140 dBA still carries risk for hearing loss. In conclusion, healthcare personnel in operating theatre were exposed to noise hazard for certain medical procedures. Hence, proper noise management should be implemented to protect them from noise-induced hearing loss while maintaining the success and efficiency of the surgeries.